Pengembangan Virtual Reality (VR) Berbasis Unity untuk Meningkatkan Pemahaman Konsep Bangun Datar Siswa Sekolah Dasar - Salsabila, Aina; Kowiyah, Kowiyah (Media Pendidikan Matematika, 2026)
Preliminary observations indicated that third-grade elementary school students still experienced difficulties in identifying and distinguishing plane shapes based on their characteristics, explaining the properties of each shape, and applying plane geometry concepts to objects in everyday life. This condition was associated with learning activities that predominantly relied on textbooks and two-dimensional media, leading students to memorize names and definitions without developing a comprehensive conceptual understanding. This study aimed to produce a Unity-based Virtual Reality (VR) learning medium that was valid, practical, and effective in improving elementary school students’ conceptual understanding of plane shapes. The study employed a Research and Development approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation. Product validity was assessed by media, subject-matter, and language experts, while practicality was evaluated through teacher responses and small- and large-group trials. Effectiveness was measured by comparing pretest and posttest scores and calculating the N-Gain. The results showed validity scores of 87% from the media expert, 90% from the subject-matter expert, and 76% from the language expert. Practicality was demonstrated by a teacher response score of 97%, a small-group student response score of 78%, and a large-group student response score of 83%. The mean conceptual understanding score increased from 66.88 on the pretest to 85.35 on the posttest, with an N-Gain of 56.49%, categorized as moderate or moderately effective. Therefore, the developed Unity-based VR medium met the criteria of validity, practicality, and effectiveness in improving elementary school students’ conceptual understanding of plane shapes